(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Coal quality indicators Coal is formed from the decomposition products of organic residues of plants that have undergone changes in the conditions of high pressure of the surrounding rocks of the earth’s crust and relatively high temperature. When the coal-bearing layer is submerged to a depth under conditions of increasing pressure and temperature, the organic mass is gradually transformed, its chemical composition, physical properties and molecular structure are changed. All these transformations are referred to by the term "regional coal metamorphism". Coal extraction methods vary depending on whether the mine is an underground mine or a surface (also called open cast) mine. Additionally coal seam thickness and geology are factors in selection of a mining method. The most economical method of coal extraction for surface mines is the electric shovel or drag line. Many coals extracted from both surface and underground mines require washing in a coal preparation plant. Technical and economic feasibility are evaluated based on the following: regional geological conditions; overburden characteristics; coal seam continuity, thickness, structure, quality, and depth; strength of materials above and below the seam for roof and floor conditions; topography (especially altitude and slope); climate; land ownership as it affects the availability of land for mining and access; surface drainage patterns; groundwater conditions; availability of labor and materials; coal purchaser requirements in terms of tonnage, quality, and destination; and capital investment requirements.